A palaeoecological and taphonomic analysis of microfossils from MIS 5 layers in Cave1, Klasies River main site, South Africa. - Faul, Inèz (My University, 2021)
Research conducted at Klasies River main site (KRM) has contributed to interpretations regarding early modern human behaviour during the Middle Stone Age in South Africa between Marine Isotope Stage (MIS) 5c-d (110–93ka). The current interpretations of the climatic and environmental background against which early human groups developed at KRM could be described in finer detail. The new excavations conducted at the main site create new opportunities for researching the paleoenvironmental context of early modern humans from perspectives not previously considered. Microfossils such as ostracods and foraminifera have been useful indicators of past environmental conditions during the Holocene in South Africa. Recent microscopic investigations revealed that ostracods and foraminifera are preserved in the KRM MIS 5 sediments from four layers dating between 100 -110 ka. The layers investigated here are layer SMONE (MIS 5c), BOS-One (MIS5d), BOS-Two (MIS 5d), and BOS-Three (MIS 5d). The abundance of the ostracods is higher during times when the site was used as primarily a knapping site with relatively less intensive occupation (in the BOS-Three layer) and is less prevalent during times of intense human occupation (in the SMONE layer). The most abundant ostracod taxon in all the layers, Gomphocythere obtusata, can be found in freshwater to slightly saline conditions, which suggests the presence of a fresh-to brackish water source nearby. The lesser abundance of ostracods in the upper layer, SMONE perhaps imply more dry conditions during the deposition of SMONE and more moist conditions during the formation of the BOS-layers. The foraminifera occur in lesser quantities and have likely been transported from outside of the KRM site
A research report submitted to the School of Geography, Archaeology and Environmental Sciences, in fulfilment of the requirements for the degree of Masters in Archaeology, at University of the Witwatersrand in 2021